Reimaging ‘the Self’ in Criminology: Transcendence, Unconscious States and the Limits of Narrative Criminology - Laws, Ben (Theoretical criminology, 2022)
Notions of ‘the self’ in criminology are rarely explored or defined, which is surprising given how pervasively the term is used. According to narrative criminology, the self is generated and moulded by the stories we tell; our identity emerges through narrative scripts and these stories motivate future action. But this understanding of selfhood is quite narrow. This article attempts to widen it by separating selfhood into three categories: ‘the reflexive self’ (the person we think we are); ‘the unconscious self’ (things we do not know that shape us); and ‘the experiencing self’ (the in-the-moment, living and breathing feeling of being alive). The article begins with a critical engagement with the field of narrative criminology which tends to address ‘the reflexive self’ somewhat in isolation. Then a number of findings in criminology, psychology and theology are presented which reveal alternative notions of selfhood. This includes engaging with theological accounts that can be described as transcendent or transpersonal. Second, psychoanalytic research notes how our behaviour is often motivated by unconscious processes that are hard to reconcile with traditional notions of selfhood. There is a call to bring these different ‘selves’ into dialogue and to draw cleaner distinctions between them. Increasing our understanding of selfhood helps us to think more clearly about key criminological debates, such as the causal mechanisms undergirding adaptation and desistance from crime.